Implementation of Software as a Service to Increase the Scalability of the Merdeka Belajar Policy in Indonesia - Soesanto, Daniel; Liliana; Louk, Maya Hilda Lestari; Handani, Felix (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Merdeka Learning is one of the breakthroughs in education carried out by the Government of Indonesia. One form of activity from Merdeka Learning is student exchange. However, not all universities in Indonesia have implemented e-learning properly due to the high cost of developing and implementing this system. Software as a Service (SaaS) is a fork of Cloud Computing that can create configurable systems for use by multiple users, especially for multi-scheme SaaS. This research develops a multi-scheme SaaS-based e-learning system with an iterative method for nine months to increase the scalability of this e-learning. Trials using the black box testing method were conducted on 15 officers and 36 students from 10 tertiary institutions. Respondents were asked to use various features of the system. The results of interviews after the trial stated that the system could assist in dealing with the online learning process at their universities. From this study, it can be concluded that multi-tenancy can be used in the development of e-learning to support the independent campus program on a website basis.